Mindfulness and acceptance approaches to sporting performance enhancement: a systematic review - Noetel, M.; Ciarrochi, J.; Van Zanden, B.; Lonsdale, C. (International Review of Sport and Exercise Psychology, 2019)
Background: Mindfulness and experiential acceptance approaches have been suggested as a method of promoting athletic performance by optimally managing the interplay among attention, cognition, and emotion. Our aim was to systematically review the evidence for these approaches in the sporting domain. Method: Studies of any design exploring mindfulness and acceptance in athletic populations were eligible for inclusion. We completed searches of PsycINFO, Scopus, MEDLINE, and SPORTDiscus in May 2016. Two authors independently assessed risk of bias using the Cochrane Risk of Bias tool, and we synthesised the evidence using the GRADE criteria. Results: Sixty-six studies (n = 3908) met inclusion criteria. None of the included studies were rated as having a low risk of bias. Compared to no treatment in randomised trials, large effect sizes were found for improving mindfulness, flow, and performance, and lower competitive anxiety. Evidence was graded to be low quality, meaning further research is very likely to have an important impact on confidence in these effects. Conclusions: A number of studies found positive effects for mindfulness and acceptance interventions; however, with limited internal validity across studies, it is difficult to make strong causal claims about the benefits these strategies offer for athletes.